181k views
5 votes
Please explain to me how to solve this problem and what would be the correct answer answer asap!!!

Please explain to me how to solve this problem and what would be the correct answer-example-1
User Madmaze
by
5.4k points

1 Answer

4 votes
Given
f(x)= -3x - 5
g(x)= 4x - 2

Find
(f - g)(x)
substitute the f and g values in (f - g)

(f - g)(x)= -3x - 5 - (4x - 2)
change the signs in parentheses because there is a negative sign in front of the parentheses

(f - g)(x)= -3x - 5 - 4x + 2
combine like terms

(f - g)(x)= -7x - 3


ANSWER: (f - g)(x)= -7x - 3

Hope this helps! :)
User Garnet
by
5.6k points